Comparison of Small-Class Versus Large-Class Tutorial Discussions - Indah Dewi Ridawati; Titi Savitri Prihatiningsih; Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: Not all small tutorial discussion groups discuss national integrated antenatal care. Tutorial discussion in a large class provide discussion together among small discussion groups of the seventh jump.Method: This study was an explanatory design, mixed-methods study. The research sample amounted to 60 students of 2.6 block in the Gadjah Mada University Bachelor Nursing Program and semi-structured interviews conducted on 10 respondents were included in the quantitative study. The data collection conducted on April 14 until June 16 2016. Antenatal knowledge instrument consists 35 multiple choice questions valid and reliable that created on antenatal module. The effect of tutorial measured after day 3 from the treatment time. Nine-eleven student in 3 small tutorial discussion groups in the different room and 30 students in a large tutorial discussion group divided into 3 small discussion groups in the same room got 4 times tutorial in 2 weeks. Materials provided include antenatal delivery.Results: Based on paired sample t test in get difference the average value of knowledge before and after the tutorial discussion, average increase of knowledge in small tutorial discussion was 0.09 (p=0.93, p<0.05) and 3.62 (p=0.02, p<0.05) in a large tutorial discussion. The qualitative data analysis showed that discussion together among small discussion groups of the seventh jump can increase knowledge acquisition.Conclusion: The results showed discussion tutorial in a large class more effective increase antenatal care knowledge acquisition than small class.